Juvenile emperor penguin range calls for extended conservation measures in the Southern Ocean - Houstin, Aymeric; Paranhos Zitterbart, Daniel; Heerah, Karine; Eisen, Olaf; Planas-Bielsa, Victor; Fabry, Ben; Le Bohec, Celine (Royal Society Open Science, 2022)
To protect the unique and rich biodiversity of the Southern Ocean, conservation measures such as marine protected areas (MPAs) have been implemented. Currently, the establishment of several additional protection zones is being considered based on the known habitat distributions of key species of the ecosystems including emperor penguins and other marine top predators. However, the distribution of such species at sea is often insufficiently sampled. Specifically, current distribution models focus on the habitat range of adult animals and neglect that immatures and juveniles can inhabit different areas. By tracking eight juvenile emperor penguins in the Weddell Sea over 1 year and performing a meta-analysis including previously known data from other colonies, we show that conservation efforts in the Southern Ocean are insufficient for protecting this highly mobile species, and particularly its juveniles. We find that juveniles spend approximately 90% of their time outside the boundaries of proposed and existing MPAs, and that their distribution extends beyond (greater than 1500 km) the species' extent of occurrence as defined by the International Union for Conservation of Nature. Our data exemplify that strategic conservation plans for the emperor penguin and other long-lived ecologically important species should consider the dynamic habitat range of all age classes.
CRIS-Team WoS Importer:2022-09-16